2021
DOI: 10.1556/004.2021.00020
|View full text |Cite
|
Sign up to set email alerts
|

Detection and molecular characterisation of feline viruses from swab samples

Abstract: Feline calicivirus (FCV), feline alphaherpesvirus 1 (FHV-1) and feline panleukopenia virus (FPLV) as well as retroviral agents such as feline leukaemia virus (FeLV) and feline immunodeficiency virus (FIV) are important viral pathogens of cats. The aim of this study was to detect and characterise FHV-1, FPLV, FeLV, FIV and feline foamy virus (FFV) in oropharyngeal, nasal and conjunctival swabs from 93 cats that had been screened for FCV previously. We wanted to determine the possible risk factors for infection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 42 publications
1
3
1
Order By: Relevance
“…Widely used vaccines protect well against the disease but do not prevent infection or developmental status of the carrier [55]. In our study, the prevalence of FHV-1 (9%; 95% CI 5.36-12.74) was low and similar to prevalence values described in Switzerland (8-9%) and Turkey (12.9%) [33,56], while lower values were found in Spain (2.6%) [57]. In contrast, significantly higher prevalence values of 61.3%, 16.3%, and 17.3% were found instead in France, China, and Australia, respectively [32,58,59].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Widely used vaccines protect well against the disease but do not prevent infection or developmental status of the carrier [55]. In our study, the prevalence of FHV-1 (9%; 95% CI 5.36-12.74) was low and similar to prevalence values described in Switzerland (8-9%) and Turkey (12.9%) [33,56], while lower values were found in Spain (2.6%) [57]. In contrast, significantly higher prevalence values of 61.3%, 16.3%, and 17.3% were found instead in France, China, and Australia, respectively [32,58,59].…”
Section: Discussionsupporting
confidence: 81%
“…Nevertheless, little is known about the molecular prevalence of FPV in cats in other regions of Italy. The molecular prevalence values reported in our study were also higher than in other studies conducted in Portugal, Egypt, Turkey, and China, where the prevalences found were 58%, 45.5%, 9.7%, and 19.2%, respectively [30][31][32][33]. A possible explanation for the high percentage of positive FPV samples we found could be related, in part, to false-positive results associated with the administration of modified live vaccine within the previous 2 weeks, as also suggested by Paris et al 2014 [34] in a study conducted in the United Kingdom.…”
Section: Discussioncontrasting
confidence: 72%
“…Three studies found that animals younger than 12 months showed a higher rate of clinical signs [ 9 , 16 , 25 ]. One study found that adults between 12 and 36 months showed a greater number of positive PCR test results for FHV [ 12 ], while Dinnage, Scarlett [ 3 ] found that geriatric cats over the age of 11 years showed a significantly higher prevalence of clinical signs. Of the remaining studies, two found no significant difference in shedding between age groups [ 31 , 32 ], two assessed the impact of age on serum antibody titres [ 33 , 34 ], and one study only reported on the effect of age in relation to vaccination status [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…Several studies reported on co-infection as a single percent of the total sample for example, Becker, Monteiro [ 39 ]) without a meaningful breakdown of the specific pathogens that were co-detected. Many studies also included several common non-respiratory feline pathogens: Abayli, Can-Sahna [ 12 ] found that FHV and FCV often co-occurred in animals with feline immunodeficiency virus (FIV) and feline panleukopenia virus (FPLV), while Bayraktar and Yilmaz [ 50 ] reported on the frequency of FHV occurring with FIV and feline leukemia virus (FeLV). It is likely that the presence of one pathogen influences the behaviour of the others, especially in high-density settings [ 25 ], yet these relationships were not assessed by any of the studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation